Strategic corporate social responsibility : stakeholders in a global environment. - Werther, William B., ....-; Chandler, David, ....- (Los Angeles : SAGE, 2011)
Blending theory with practical application, this comprehensive text supports courses at the intersection of corporate social responsibility (CSR), corporate strategy, and public policy. Part I provides an overview of the field, defining CSR and placing it in the context of wider corporate strategy. Part II contains chapters on CSR issues related to the organization, the economy, and society, and provides detailed case studies on a variety of well-known firms. Adopting a stakeholder perspective, the authors explore CSR issues within the complex global business environment in which corporations operate today.
Keywords: Ethisch ondernemen